Concrescence: can the teeth involved be moved or separated? - Alberto Consolaro; Omar Hadaya; Dario A. Oliveira Miranda; Renata Bianco Consolaro (Dental Press Editora, 2020)
ABSTRACT The atrophy of the periodontal ligament places the tooth very close to the bone or another tooth, as occurs in unerupted teeth. The absent interdental bone and the lack of functional periodontal stimulus may lead to the fusion of the appositional layers of cement between the roots of the teeth. Concrescence almost always occurs in the region of the maxillary molars. Asymptomatic, it should always be remembered when the proper response to orthodontic movement is not obtained, and there is no apparent explanation. When surgically extracting a tooth and there is resistance, insisting will not be the best strategy. Moving the teeth with concrescence is not convenient, as it requires very intense forces. Once separated, these teeth can be considered normal for movement. It is possible to separate two teeth presenting concrescence, but it depends on the extension of the area, the surgical access and, especially, the clinical convenience. The tooth to be extracted will be repaired with new cement deposited in the sectioned area. The simple separation with the maintenance of the proximity and the lack of function of one of the teeth will cause a new concrescence. After a period of 1 to 3 months, the separated teeth are biologically prepared to be moved. The most important detail in this separation of teeth presenting concrescence is that the diagnosis should be made in advance, and not at the time of the intervention.